Sekundo's Applanator: 5 Years of Experience With Transconjunctival Suturing. Issue 2 (February 2017) - Elbaz, Hisham; Sekundo, Walter; Schröder, Frank-Michael; Schulze, Stephan
Abstract : Sekundo's Applanator is a new surgical instrument used mainly in transconjunctival scleral flap suturing in cases of postoperative hypotony after trabeculectomy. In contrast to Hoskins lens, it offers better visualization of the border of the scleral flap with good intraoperative stabilization of the globe; thus, it increases the effectiveness and decreases the time of the surgical procedure. Sekundo's Applanator was also found to be useful in reducing the size of an oversized bleb after trabeculectomy and in the closure of leaking sutureless sclerotomies after vitrectomies. In this report, we present and discuss the properties, uses, and advantages of this new instrument to the ophthalmic community.